INNOVATIONS IN LEADERSHIP: TRENDS AND EXPERIENCE FOR UKRAINE (INNOVATIVE ECONOMY, 2025)
Izhevskyi P.H., Fedoryshyna L.M. INNOVATIONS IN LEADERSHIP: TRENDS AND EXPERIENCE FOR UKRAINEPurpose. The aim of the article is to research on the transformation of approaches to leadership in modern conditions, identification of key innovation trends, challenges and features of its manifestation in the world and Ukraine.Methodology of research. The following general and special research methods were used to achieve the set goal, in particular: analysis, monographic, abstract and logical, generalization – to consider the essence of approaches to leadership (both traditional and innovative), to formulate the reasons for the emergence of new approaches to leadership, to outline the areas that modern leaders should work on; graphic and tabular – to present the author's vision and better visualize the results of the conducted study regarding innovative approaches to leadership support, measures for forming staff involvement and trust.Findings. The transformation of approaches to leadership in modern conditions was determined. Traditional and new approaches to leadership were generalized, and their characteristics were given. The reasons for the emergence of new approaches in leadership were established: global crises and the war in Ukraine, a high level of uncertainty and turbulence in the environment, the rapid development of digital technologies, changing values of society and generations, the growing role of communications and teamwork, trends towards sustainable development. It is substantiated that important trends in leadership in modern conditions should be called: the need to build trust in management; increasing the involvement of ordinary employees; searching for and retaining talents with leadership qualities; ensuring the effectiveness of combining humans with artificial intelligence and its integration into all areas of the company's activities. A list of unique features of Ukrainian leaders that appeared during the war has been formed.Originality. The study of the process of leadership transformation in modern conditions, in particular innovative approaches and challenges that have emerged in recent years, as well as its specific manifestations in Ukraine, has received further development.Practical value. The results of the conducted research can become the basis for further scientific research on the possibility of adapting the experience of leading companies in increasing staff engagement and trust by the management of Ukrainian enterprises, adjusted for the specific operating conditions.Key words: leadership, innovation, trust, engagement, empathy, artificial intelligence, key skills, manager, leader.
Keywords: leadership; innovation; trust; engagement; empathy; artificial intelligence; key skills; manager; leader